PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP MANAJEMEN WAKTU BELAJAR DIMASA PANDEMI - Putu Sri Andini, Ida Ayu (Jurnal Bimbingan dan Konseling Pandohop, 2022)
The purpose of this study was to describe the understanding and activities of class VIII SMP Kesatuan Bogor in participating in classical guidance services during the Bombingan Counseling lesson with the PBL learning model. This research is a classroom action research conducted in 1 cycle consisting of 1 meeting. This research was conducted in the 8th grade of SMP Unit Bogor. The data collection technique used observation, interview and questionnaire techniques, while the data analysis used descriptive qualitative analysis. Observation techniques were used to determine student activities in participating in learning and questionnaires were used to describe students' understanding of learning during learning with the PBL model. The results of this study indicate an increase in students' understanding of learning and learning activities from the initial conditions. This increase shows the success of implementing the PBL learning model, thus it can be concluded that increasing students' understanding of learning time management during the pandemic through the PBL learning model has been successfully carried out.